The familiar area hypothesis and movement patterns of wild forest reindeer in Karelia, Northern Europe - Pulliainen, E.; Danilov, P. I.; Heikura, K.; Erkinaro, E.; Sulkava, S.; Lindgren, E. (Rangifer, 1986)
The relevance of the familiar area hypothesis to the behaviour of the wild forest reindeer (Rangifer tarandus fennicus Lönnb.) was studied in a Fenno-Soviet project by radio and field tracking of these ungulates in Karelia, Northern Europe, in 1978 - 1985. This subpopulation (500 - 600 exx.) has a tradition of overwintering in a restricted area around Lake Lentua (ca. 1000 km2). The spring migration period is shorter in length than the autumn migration. The migration routes are generally the same in autumn and spring, although exceptions occur, indicating exploratory behaviour. The large winter herds disband into small groups or lone individuals for the summertime, when this subpopulation is spread over a much wider area (ca. 5400 km2). It is concluded that the observations made support the familiar area hypothesis in all essential points.